HOW TO ACHIEVE IMPROVING THE FARMER SHARE WITH MODEL SUPPLY CHAIN MANAGEMENT FOR SME’s TEMPE – TOFU LAMPER TENGAH - Azis Fathoni (Jurnal Ekonomi dan Bisnis Kontemporer, 2017)
Information systems through the model of the use of Supply Chain Management model for SME’s Tofu Tempe “Gumregah” Lamper Tengah became as Base Knowledge to use recently. The problem at this time is the price of soybean as the main raw material is very expensive and must be imported from the USA and there is no alternatie raw materials and from other suppliers. Implementation of information technology from Hulu – Hilir raw material as the main supply chain of tempe-tofu production will become the basis of Home Ekonomic management for members of the community that know SME’s ownersThe main target of information technology on supply chain management is to refer maintain this small business continuity. This study aims to analyze the knowledge of Supply Chain Management which is often known as Supply Chain Management (SCM) which is expected to improve the handling of good raw materials and decrease the allocation of raw materials management cost.The results of research show that supply chain management strategy used is to use mix 1 supplier and 2 – 3 suppliers. Many Small Businesses Tofu - Tempe is developing their own supply chain in a different context than the traditional supply chain. Looking at the supply chain developed by SME’s Tempe - Tofu Lamper Tengah shows different process innovations to meet the needs and ultimate consumer satisfaction. It also results in innovation and product innovation processes in delivering goods to end users.It also identifies the different processes and product innovations generated from a marketing perspective to put the end consumer first. The study was conducted using interviews with SME’s who are beneficiaries of Bapedda Kota Semarang. Data collected through actual observations on the implementation of the Great Gateway Concept (GERBANG HEBAT) of Semarang City.Key Words: Information System, Raw Material, Continuity, End User